Facilitating Qur'anic Literacy in Early Childhood through Smart Hafiz “Al Qolam” - Taufikin, Taufikin (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2025)
The introduction of Qur'anic literacy from an early age is necessary in contemporary Islamic education. However, conventional approaches to teaching Qur'anic literacy often face various limitations, especially in maintaining children's interest in learning. This study examines the effectiveness of Smart Hafidz "Al Qolam" as an interactive digital media in supporting the mastery of hijaiyyah letters, reading fluency, and memorization of short letters in early childhood. This research method employed a descriptive quantitative approach to 22 children aged 4-6 years who were active users of Al Qolam for six months in TK Mawarbudi 1 and 2, Harjowinangun, Demak District. Data were collected through direct observation and assessment of children's Qur'anic skills. The results showed that all participants successfully mastered the hijaiyyah letters. Six children could read the Qur'an fluently, ten showed moderate fluency, and the remaining six could recognize letters well, although they did not read thoroughly. In addition, most children memorized at least five short surahs. Al Qolam's voice and interactivity features increased child engagement and created a more enjoyable learning experience in the home environment. This study confirms that digital tools, such as Al Qolam, have significant potential to strengthen the Qur'anic literacy foundation and can be broadly integrated into early childhood education.